The impact of Responsible Leadership on Organizations - Matos, Maria Helena Silva; Pais, Leonor; Santos, Nuno (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
In the 21st century, we see a growing awareness of a range of pressing, global and systemic problems that threaten the stability of ecological, social communities, and vital economic systems. We face challenges such as climate change, overexploitation of resources, ecological problems, social aspects, a rapid loss of biodiversity, and continued poverty, requiring structural and cultural changes and a global shift towards more responsible, sustainable, and equitable economies and societies. As long as the traditional leadership approach emphasizes dominance, manipulation, and dependency, it has been widely criticized and considered less effective than responsible, ethical, and humane practices. Organizations and their leaders are increasingly held accountable for what they do and do not do by the various stakeholders and society. Leaders are expected to assume a more active role and recognize their co-responsibility in current problems, such as promoting human rights, guaranteeing sustainability, and contributing to the reduction of poverty (Voegtlin, 2011). Leaders are constantly challenged to lead with a sense of responsibility (Haque et al., 2017). It has been argued that leadership should have a global approach that integrates all areas of the organization, which allows not only to change the world and society but also to reinforce innovation and profitability. It is increasingly expected that organizations' leaders not only assume their commitments to the company's shareholders but also respond to society and the environment (Voegtlin, 2011). The individual leadership style is a determining factor for organizational results of effectiveness, innovation, success, and sustainability. Responsible leadership has gained increased attention in several organizational studies (Haque et al., 2017). Several authors argue that the adoption of a responsible leadership style by leaders will allow them to respond effectively to the challenges imposed, as the responsible leader builds and maintains positive relationships with the various stakeholders (Doh & Stumpf, 2005; Maak & Pless, 2006; Voegtlin, 2011; Haque et al., 2019), which promotes the achievement of desirable results (Voegtlin et al., 2012). Responsible leadership is defined as leadership based on values, ethically thought out and executed decisions, and a quality relationship with stakeholders (Doh & Stumpf, 2005; Muff et al., 2020). Moreover, Responsible Leadership refers to the process and ability to create and mediate relationships of trust between the various stakeholders so that shared objectives can be achieved based on the implementation of conducts for a meaningful and shared business vision (Maak, 2007), and based on the pillars of ethics, sustainability, and responsibility (Cameron, 2011; Doh et al., 2011). Responsible leadership fits the organization's activity into a broader ecosystem in order to strengthen the organization's constructive role in society at large. Responsible leaders promote solid social ties in the workplace and maximize human potential by promoting a positive work environment, climate, and communication (Cameron & Caza, 2005). The various HRM practices have been gaining increasing importance concerning the impact on people's attitudes and the alignment of these same attitudes with the organization's strategy (Bowen & Ostroff, 2004), while leadership has been highlighted as a driver and influencer of behaviors (Bakker, 2017). Adopting responsible leadership promotes positive work environments (Haque, 2017), where workers feel heard and can participate in different areas of the organization, leading to a strong connection with it (Voetgtlin et al., 2012). Some studies have found a positive and significant relationship between responsible leadership and the person-organization fit (Huang et al., 2005). In addition, responsible leaders drive employees to perform better at work through increased psychological involvement (Yafi et al., 2021), as they set positive examples, establish effective communication, and inspire people to get involved at work in order to achieve positive organizational results (Doh and Quigley, 2014).